Unravelling the Role of Candida albicans Prn1 in the Oxidative Stress Response through a Proteomics Approach - Victor Arribas; Lucia Monteoliva; María Luisa Hernáez; Concha Gil; Gloria Molero (MDPI AG, 2024)
Candida albicans Prn1 is a protein with an unknown function similar to mammalian Pirin. It also has orthologues in other pathogenic fungi, but not in Saccharomyces cerevisiae. Prn1 highly increases its abundance in response to H2O2 treatment; thus, to study its involvement in the oxidative stress response, a C. albicans prn1∆ mutant and the corresponding wild-type strain SN250 have been studied. Under H2O2 treatment, Prn1 absence led to a higher level of reactive oxygen species (ROS) and a lower survival rate, with a higher percentage of death by apoptosis, confirming its relevant role in oxidative detoxication. The quantitative differential proteomics studies of both strains in the presence and absence of H2O2 indicated a lower increase in proteins with oxidoreductase activity after the treatment in the prn1∆ strain, as well as an increase in proteasome-activating proteins, corroborated by in vivo measurements of proteasome activity, with respect to the wild type. In addition, remarkable differences in the abundance of some transcription factors were observed between mutant and wild-type strains, e.g., Mnl1 or Nrg1, an Mnl1 antagonist. orf19.4850, a protein orthologue to S. cerevisiae Cub1, has shown its involvement in the response to H2O2 and in proteasome function when Prn1 is highly expressed in the wild type.